Inhibition of Angiopoietin-2 Production by Myofibrocytes Inhibits Neointimal Hyperplasia After Endoluminal Injury in Mice - Chen, Daxin; Li, Ke; Tham, El-Li; Wei, Lin-Lin; Ma, Ning; Dodd, Philippa C.; Luo, Yi; Kirchhofer, Daniel; McVey, John H.; Dorling, Anthony (Frontiers in Immunology, 2018)
Fibrocytes are myeloid lineage cells implicated in wound healing, repair and fibrosis. We previously showed that fibrocytes are mobilized into the circulation after vascular injury, including the immune-mediated injury that occurs after allogeneic transplantation. A common response to inflammatory vascular injury is intimal hyperplasia (IH), which, alongside vascular remodeling, results in progressive loss of blood flow, downstream ischaemia and end-organ fibrosis. This forms the pathological basis of transplant arteriosclerosis and other diseases including post-angioplasty re-stenosis. In investigating whether fibrocytes contribute to IH, we previously showed that subpopulations expressing smooth muscle actin and CD31 are recruited to the site of injury and accumulate in the neointima. Expression of tissue factor (TF) by these ‘CD31+ myofibrocytes’ is needed for progressive neointimal expansion, such that TF inhibition limits the neointima to a single layer of cells by day 28 post-injury. The aim of this study was to determine pathophysiological mediators downstream of TF that contribute to myofibrocyte-orchestrated IH. We first show that myofibrocytes make up a significant component of the neointima 28 days following injury. Using a previously defined adoptive transfer model, we then show that CD31+ myofibrocytes get recruited early to the site of injury; this model allows manipulations of the adoptively transferred cells to study how IH develops. Having confirmed that inhibition of TF on adoptively transferred cells prevents IH, we then show that TF, primarily through the generation of thrombin, induces secretion of angiopoietin-2 by myofibrocytes and this directly stimulates proliferation, inhibits apoptosis and induces CXCL-12 production by neointimal cells, including non-fibrocytes, all of which promote progressive IH in vivo. Prior incubation to inhibit angiopoietin-2 secretion by or block TIE-2 signaling on adoptively transferred fibrocytes inhibits IH. These novel data indicate that angiopoietin-2 production by early recruited myofibrocytes critically influences the development of IH after vascular injury and suggest new therapeutic avenues for exploration.